Answer:
The volume of the cylinder is <u>141.23 cubic feet </u>
Step by step explanation :
<u>Given</u>-
- Radius of cylinder = 3 feet
- Height of cylinder = 5 feet
Now, we know that
<h3>
![\boxed {\mathfrak \red{ volume \: of \: cylinder = \pi {r}^{2} h}}](https://tex.z-dn.net/?f=%20%5Cboxed%20%7B%5Cmathfrak%20%5Cred%7B%20volume%20%5C%3A%20of%20%5C%3A%20cylinder%20%3D%20%5Cpi%20%7Br%7D%5E%7B2%7D%20h%7D%7D)
</h3>
where, r is the radius of the cylinder & h is the height of the cylinder.
Now,
Volume of the cylinder = ![\frac{22}{7} \times {3}^{2} \times 5](https://tex.z-dn.net/?f=%20%5Cfrac%7B22%7D%7B7%7D%20%20%5Ctimes%20%20%7B3%7D%5E%7B2%7D%20%20%5Ctimes%205)
![= \frac{22}{7} \times 3 \times 3 \times 5](https://tex.z-dn.net/?f=%20%3D%20%20%5Cfrac%7B22%7D%7B7%7D%20%20%5Ctimes%203%20%5Ctimes%203%20%5Ctimes%205)
<h3>
![= \frac{990}{7}](https://tex.z-dn.net/?f=%20%3D%20%20%20%5Cfrac%7B990%7D%7B7%7D%20)
</h3>
( approximately )
![= \boxed{ 141.43 \: \mathfrak { {ft}^{3}} }](https://tex.z-dn.net/?f=%20%3D%20%20%5Cboxed%7B%20141.43%20%5C%3A%20%20%5Cmathfrak%20%7B%20%7Bft%7D%5E%7B3%7D%7D%20%7D)
If you are graphing quadratic equations of the type
ax^2 + bx + c = 0
The equation will look like a "U" <span>if "a" is positive </span>or it will look like an upside-down "U" <span>if "a" is negative </span>
Cos(theta) = adjacent/hypotenuse
cos(theta) = 6/20
cos(theta) = 0.3
Use the inverse cos or cos^-1 on your calculator to get the angle
theta = 72.5
Answer:
27a
Step-by-step explanation:
-5(a-6)+2a
-5a+30+2a
-3a+30
27a
2x - 4y + 1z = 11 ⇒ 2x - 4y + 1z = 11
1x + 2y + 3z = 9 ⇒ <u>1x + 2y + 3z = 9</u>
3x + 5z = 12 1x - 2y - 2z = 2
1x - 2y - 2z = 2
2x - 4y + 1z = 11 <u>-2x + 2y - 2z = -3</u>
1x + 2y + 3z = 9 ⇒ 1x + 2y + 3z = 9 x - 4z = 1
3x + 5z = 12 ⇒ <u>3x + 5z = 12</u> x - 4z + 4z = 1 + 4z
-2x + 2y - 2z = -3 x = 1 + 4z
<u /> 1 + 4z - 2y - 2z = 2<u />
1 - 2y + 4z - 2z = 2
1 - 2y + 2z = 2
<u>- 1 - 1</u>
-2y + 2z = 1
-2y + 2z - 2z = 1 - 2z
<u>-2y</u> = <u>1 - 2z</u>
-2 -2
y = -0.5 + z
x + 2(-0.5 + z) - 2z = 2
x - 1 + z - 2z + 2 = 2
x - 1 + z = 2
<u> + 1 + 1</u>
x + z = 3
x - x + z = 3 - x
z = 3 - x
<u />